1999
DOI: 10.1002/(sici)1099-0968(199903)7:1<37::aid-erv254>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of the family relations scale to a sample of anorexics, bulimics and non-psychiatric controls: a preliminary study

Abstract: The role of the family in the pathogenesis and treatment of eating disorders is an area of extensive and ongoing research. Numerous scales for measuring various aspects of family functioning exist. The study employed the Family Relations Scale (FRS) in a sample of 17 eating disordered patients, and their families, diagnosed in a hospital setting using DSM IV criteria (anorexia nervosa: n 10; bulimia nervosa: n 7) and 20 non-psychiatric controls and their families. The families within the groups were remarkably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As seen until now thanks to the contribution of empirical studies on family factors in eating disorders, in particular, those that have used the FACES-IV instrument [85][86][87] family models multi-determined and contextual psychopathological processes in developmental age is gaining ground. All the results of the studies indicate a shift from a focus on family deficits towards family resources, which is a gradual encouragement of family skills and positive connections between members [74].…”
Section: A Possible Integrate Perspective For Understanding Eating DImentioning
confidence: 93%
See 2 more Smart Citations
“…As seen until now thanks to the contribution of empirical studies on family factors in eating disorders, in particular, those that have used the FACES-IV instrument [85][86][87] family models multi-determined and contextual psychopathological processes in developmental age is gaining ground. All the results of the studies indicate a shift from a focus on family deficits towards family resources, which is a gradual encouragement of family skills and positive connections between members [74].…”
Section: A Possible Integrate Perspective For Understanding Eating DImentioning
confidence: 93%
“…Even in the most recent studies, results concerning the evaluation of family functioning among the different diagnostic categories of eating disorders are divergent. Some studies have shown no significant differences between the diagnostic categories of eating disorders [74,75]. Other studies have found significant differences between the types of eating disorders in relation to different elements of family functioning: For example, cohesion and orientation to achievement were found to be worse in families with anorexia, compared to bulimic families [73].…”
Section: Contemporary Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eisler et al, 2003;Le Grange and Eisler, 2008;Lock et al, 2006) Family functioning has been measured both as a unitary construct reflecting the general functioning of the family as a whole and as a set of several aspects, such as flexibility, cohesion, and communication. Existing evidence suggests that there is a substantial agreement within family members dealing with AN in perceiving an impairment of the general family functioning and a strong dissatisfaction with family life (Casper and Troiani, 2001;Ciao et al, 2015;Cook-Darzens et al, 2005;Emanuelli et al, 2004;McDermott et al, 2002;Szabo et al, 1999); on the other hand, when considering specific dimensions of family functioning, significant differences are found between girls with AN and their parents, even though research shows variable and sometimes conflicting results (Ciao et al, 2015;Holtom-Viesel and Allan, 2014).…”
Section: According To the Diagnostic And Statisticalmentioning
confidence: 99%
“…Regardless, some theoretical models and data have led to the assumption that impaired family structure and functioning can play an important part in the etiology and maintenance of the ED (Bonne, et al, 2003;Cook-Darzens, et al, 2005). Studies following this model have shown that families of patients with an ED generally tend to be less cohesive, more 5 overprotective, more rigid and to have poorer communication than healthy control families (Eisler, 2005;Szabo, Goldin, & Le Grange, 1999;Vidović, et al, 2005). Regarding gender differences, some studies gave shown that in comparison to fathers, mothers of patients with Anorexia Nervosa (AN) view their families to be more rigid, whereas fathers seem to be as more satisfied with their family life than other family members (Cook-Darzens, et al, 2005).…”
Section: Gender Differences In Parent Functioning As An Antecedent Inmentioning
confidence: 99%